REFLECTION AS A MEANS FOR LEARNING SKILL IMPROVEMENT IN STUDENTS - Kāposta, Iveta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Self-regulation is one of the criteria in good or competent learning. Self-regulated learning means that the learning person understands the process of one's learning i.e. understands what one needs; understands what happens to one during such learning; one is responsible for own learning; one has acquired and independently applies learning skills. Many scholars regard reflection as being means for improvement of competent learning. Reflection in pedagogy is to be understood as a process of awareness the performance and / or action which took place in educational process or any part. Reflection is based on analysis of one's actions and/or activities. Reflection may differ both in terms of the goal as well as in terms of the subject across various stages of learning process and activities. Russian educator and psychologist A. Stepanova classifies reflection in accordance with the subject of reflection (Степанова, 2009): mood and emotional status reflection; reflection of learning content; learning activity reflection. Mood and emotional status reflection and learning content reflection are often applied in Latvian schools; while reflection on learning activities has enjoyed little recognition. Educators in Latvian schools often offer students use questions and visualisation as methods of reflection (latter is used in work with younger students), but negotiations are offer relatively rare. Educators recognise reflection better according to the actions but they lack knowledge on reflection during action thus not offering it to students. Nevertheless, some secondary education students use reflection during action in an unaware manner. Reflection on average is given 5 - 10 minutes during a lesson.